Prognostic Indicators for Positive Treatment Outcome After Multidisciplinary Orofacial Treatment in Patients With Somatosensory Tinnitus - van der Wal, Annemarie; Van de Heyning, Paul; Gilles, Annick; Jacquemin, Laure; Topsakal, Vedat; Van Rompaey, Vincent; Braem, Marc; Visscher, Corine Mirjam; Truijen, Steven; Michiels, Sarah; De Hertogh, Willem (Frontiers in Neuroscience, 2020)
Introduction: Subjective tinnitus, influenced by the somatosensory system is called somatosensory tinnitus (ST). When ST is related to the temporomandibular area, multidisciplinary orofacial treatment can reduce tinnitus severity. It is however unknown if we can predict this positive outcome.The aim of this study is to look for prognostic indicators that can predict a positive outcome after multidisciplinary orofacial treatment in patients with ST. Methods: Patients were included when they were diagnosed with temporomandibular related ST and received a maximum of 18 sessions of orofacial treatment during a 9-week program. Predictors for positive treatment outcome were identified using univariate and multiple logistic regression analyses with the Tinnitus Questionnaire (TQ) and the Tinnitus Functional Index (TFI) as dependent variable. Results: The results of 101 patients were included in the analysis. Immediately after multidisciplinary orofacial treatment, a clinically relevant decrease on TQ-score was significantly associated with ‘shorter duration of the tinnitus’ (OR 0.99), ‘higher initial score on the TQ somatic subscale’ (OR 1.52) and ‘painfull palpation of temporomandibular joint (TMJ)’ (OR 2.46). After 9 weeks follow-up, the ‘higher initial score on the TQ somatic subscale’ remained the sole predictor (OR 1.44). A clinically relevant decrease on TFI after 9-weeks follow-up, was predicted by ‘female gender’ (OR 2.70), ‘younger age’ (OR 0.96), ‘shorter duration of the tinnitus’ (OR 0.99), ‘lower pressure pain thresholds’ on TMJ’ (OR 0.99), ‘lower PPT on sternocleidomastoideus’ (OR 0.99) and ‘better speech in noise perception’ (OR 0.88). A multivaritate model consisting of ‘shorter duration of the tinnitus’ and ‘higher initial score on the somatic subscale of the TQ correctly predicts the clinically relevant decrease in TQ-score after treatment in 68.5%. A second multivariate model consisting of ‘female gender’, ‘younger age’ and ‘shorter duration of the tinnitus’ correctly predicts a clinically significant decrease on TFI after follow-up in 68.1%. Conclusion: We were able to indentify various prognostic indicators. ‘Younger female patients’ with a ‘shorter duration of the tinnitus’ and a ‘higher initial score on the TQ somatic subscale’, are the most consistent indicators with the highest predictive value.